THE IMPACT OF SOCIAL NETWORKS ON THE EMERGENCE OF NEW ENGLISH WORDS AND THEIR SEMANTIC ANALYSIS - Sarvinoz Jiyanboyeva; Charos Iriskulova (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: This article analyzes new lexical units emerging in the English language under the influence of social media and their semantic changes. The study explores the formation methods of internet neologisms and their role in modern communication.